Thermal and rheological properties of starch-based materials. (February 2019) - Liu, F S; Lu, K; Shao, Z Z; Shi, K L; Lin, X Y; Liu, H S; Yu, L
Abstract: From application-oriented point of view, in order to decrease the cost of transportation the starch-based form was prepared by two steps: 1) compounding; and 2) foaming. That is because the foamed materials consist of more than 90% gas, the transportation cost could be higher than foam itself. In this work, starch-based pallets used for foaming were developed by extrusion. This presentation focuses on thermal and rheological properties of the starch-based materials. Cornstarch was used in this work. The results showed that the gelatinization temperature of the cornstarch was about 68°C with excess water content. The shear thin rheological behavior was observed for the cornstarch. Based on these the extrusion condition were designed and developed. In order to avoid foaming during compounding the temperature should be controlled less than 100°C. The higher screw speed can reduce the processing energy.